Internet of Bodies, datafied embodiment and our quantified religious future - Zheng Liu (HTS Teologiese Studies/Theological Studies, 2023)
This article discusses the datafied embodiment of the Internet of Bodies (IoB) technology by applying the methodology of postphenomenology. Firstly, the author claims that the boundaries of dual distinction between real and virtual, online and offline, and embodiment and disembodiment have become increasingly blurred. Secondly, the author argues that postphenomenology can help us to study today’s emerging technologies’ mediating role in human–world relations. Thirdly, the author analyses the implication of embodiment from phenomenological and postphenomenological perspectives and then demonstrates in what sense the data collected from the IoB devices can constitute our embodiment and selfhood. Fourthly, the author elucidates how the IoB devices are datafying our bodies and the whole lifeworld and how these devices mediate and transform our religious practices and experiences. Fifthly, the author points out that the Quantified Religion as the possible new religious model would smooth out the differences and diversities between religions and then create homogeneous religious data selves, which will mediate, reshape, constitute and even replace our physical selves. Ultimately, the author argues that responsible designing of the IoB devices and establishing the ownership of personal religious data can be seen as significant measures in the face of the risk of our quantified religious future.